The moral economy of the Didache - Jonathan A. Draper (HTS Teologiese Studies/Theological Studies, 2011)
This article applies the model of the moral economy in the ancient world, as formulated by Karl Polanyi and applied by Halvor Moxnes, to the economic relations reflected in the Didache. The study partly confirms Aaron Milavec’s contention that the instructions in the text would provide an ‘economic safety net’ for members of the community by putting in place a system of generalised reciprocity and redistribution, although Milavec’s depiction of the community as an ‘urban working class’ movement is found to be anachronistic. The ‘communion of the saints’ is very much an economic system with aspects of resistance to the Roman imperial system. However, the moral economy of the Didache is seen to reflect a number of ambiguities, particularly in its adoption of the Christian Housetable ethic but also in its adoption of the patron client terminology in the dispute between prophets and teachers on the one side and bishops and deacons on the other.